Association between oxidative balance scores and all-cause and cardiovascular disease-related mortality in patients with type 2 diabetes: data from the national health and nutrition examination survey (2007-2018) - Hao Wang; Yan-Lin Chen; Xiang-Ming Li; Qi Wu; Yan Xu; Jin-Song Xu (BMC, 2024)
Abstract Background Oxidative Balance Scores (OBS) is composite measures that assess the balance between pro-oxidant and antioxidant factors in an individual's diet and lifestyle. Evidence on OBS and cardiovascular disease (CVD) in diabetic patients is scarce. This study investigates the potential association between OBS and CVD-prevalence and all-cause and CVD-related mortality in adult diabetic patients. Methods Participants were selected from the National Health and Nutrition Examination Survey (NHANES) 2007-2018. OBS-related data collection was initiated by linking the National Death Index to determine mortality due to all-cause and cardiovascular disease until December 31, 2019. Weighted logistic regression analyses explored the relationship between OBS and CVD. In addition, multivariable Cox proportional risk regression models and Kaplan-Meier curves were used to determine the correlation between OBS and mortality, with time to event as the time variable, as well as to estimate hazard ratios (HR) and 95% confidence interval (CI). Results A total of 3491 participants were included in the final analysis. Weighted logistic regression analysis of the relationship between OBS and CVD prevalence found that higher OBS was not associated with CVD prevalence compared with lower levels after fully adjustment in model 3 (OR: 0.82, 95% CI: 0.51-1.31, P = 0.39). During 3,491 person-years of follow-up, 408 deaths were recorded, of which 105 deaths were attributed to CVD. In fully adjusted model 3, participants in the highest quartile of OBS had significant reductions in all-cause mortality of 53% [HR: 0.47, 95% CI: 0.29-0.77), Ptrend= 0.002] and in cardiovascular disease mortality of 78% [HR: 0.22, 95% CI: 0.08-0.56), Ptrend= 0.004], compared with the lowest quartile groups of OBS. The Kaplan-Meier analysis results showed that participants in the highest quartile of OBS had the lowest risk of all-cause and CVD-related mortality and were statistically different (P < 0.05). Subgroup analysis confirmed that P for interaction was significant only concerning the educational level attained and in individuals with a history of CKD (P < 0.05). Conclusions Although OBS wasn't very useful for assessing CVD prevalence outcomes, higher OBS was significantly associated with lower all-cause and CVD-related mortality, suggesting that maintaining adequate OBS may reduce mortality in patients with DM. Graphical Abstract